Comparision study of antioxidant in commercial juice drinks using DDPH scavenging activity and total phenolic compound (TPC) / Hasrulnizam Abd Hamid - Abd Hamid, Hasrulnizam (Faculty of Applied Sciences, 2009)
The study of the present project was to determine and compare the antioxidant activity in commercial juice drinks using DDPH scavenging activity and Total Phenolic Compound (TPC). Samples analysed were from the same brand (Marigold product) namely: orange juice, guava juice, apple juice and mango juice. The order of effectiveness of fruit juices in inhibiting free radicals was as follow: apple juice, (92.81%) > orange juice, (84.85%) > guava juice, (79.02%) > mango juice, (65.48%).The values of total phenolic compounds in the juice were as follows: mango juice, (578.1 mg GAE/L) > orange juice, (381.8 mg GAE/L) > guava juice,( 230.8 mg GAE/L) > apple juice,( 228.5 mg GAE/L).